Post Typhoid Ileum Perforation - Teaching Assistant, Dr Samiullah Sajjad; Teaching Assistant, Dr Israrullah Rahimee (IJRDO-Journal of Applied Science, 2021)
Post typhoid ilium perforation is still prevalent in many developing countries. Despite the advances in The management, the outcome in these patients in resource limited countries is still very poor. Despite various measures such as safe drinking water supply and safe disposal of waste, intestinal perforation from salmonellosis remains the most common emergency surgery performed. The incidence continues to rise, so also the mortality, despite new antibiotics and improvement in surgical technique This topic review was to review our experiences on to determine the prevalence, prognostic factors, morbidity, mortality and surgical management of post typhoid ilium perforation. The purpose of this topic review was to describe the prevalence, prognostic factors, morbidity, mortality and surgical management of post typhoid ilium perforation. We hoped that identification of this topic will help in prioritizing management and improving the quality of care in post typhoid ilium perforation. This topic is reviewed the recently published articles at high prestigious (PubMed, BMJ، GHN، CDC, Medical books, Net &, etc. ) based on different (case control,retrospective,prospective… ) clinical studies about post typhoid ilium perforation . Ilium perforation is still common and lethal complication of typhoid in endemic area. The ilium perforation represented about 8.5% of typhoid which need to emergency laparotomy. In this topic review has more information about post typhoid ilium perforation from many recent articles like describe below.